2016
DOI: 10.3758/s13414-016-1091-x
|View full text |Cite
|
Sign up to set email alerts
|

Inattentional blindness: A combination of a relational set and a feature inhibition set?

Abstract: Two experiments were conducted to directly test the feature set hypothesis and the relational set hypothesis in an inattentional blindness task. The feature set hypothesis predicts that unexpected objects that match the to-be-attended stimuli will be reported most. The relational set hypothesis predicts that unexpected objects that match the relationship between the to-be-attended and the to-be-ignored stimuli will be reported the most. Experiment 1 manipulated the luminance of the stimuli. Participants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 18 publications
(41 reference statements)
2
14
0
Order By: Relevance
“…Rather than enhancing "white" and suppressing "black," the attention set might enhance "lighter" and suppresses "darker." When display objects are red-orange and yellow-orange, and subjects are instructed to attend to the "redder" set, they unsurprisingly notice unexpected red-orange objects (Goldstein & Beck, 2016). However, they also notice extreme examples of the relation (red when attending to "redder" or yellow when attending to "yellower") just as often as exact color matches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than enhancing "white" and suppressing "black," the attention set might enhance "lighter" and suppresses "darker." When display objects are red-orange and yellow-orange, and subjects are instructed to attend to the "redder" set, they unsurprisingly notice unexpected red-orange objects (Goldstein & Beck, 2016). However, they also notice extreme examples of the relation (red when attending to "redder" or yellow when attending to "yellower") just as often as exact color matches.…”
mentioning
confidence: 99%
“…Red objects and red-orange objects are both "redder" than yellow-orange objects, but also featurally similar to each other and dissimilar from the ignored objects (Goldstein & Beck, 2016). To determine which aspect of similarity drives the effects of attention sets on noticing, an experiment must isolate each possible mechanism, eliminating other ways to parse the display.…”
mentioning
confidence: 99%
“…In this case, subjects rarely notice black, but often notice white; the pattern reverses when subjects attend gray and ignore white instead (Most et al, 2001). A replication of this experiment including gray unexpected objects found the same pattern: when ignoring black and attending gray, subjects noticed gray and white unexpected objects more than black ones, and when attending gray and ignoring white, they missed white but noticed gray and black (Goldstein & Beck, 2016). More generally, people tend to notice any color that differs from those which they are ignoring (Drew & Stothart, 2016; see Figure 1).…”
Section: Introductionmentioning
confidence: 56%
“…This finding reflects that UEO in the best relation-matched condition is more likely to capture attention when available attentional resources are scarce. However, unlike the spatial blink task (Du & Jiao, 2016;Du et al, 2014), there is no stringent spatial control in the inattentional blindness task of Goldstein and Beck's (2016) study. Goldstein and Beck's finding did not address whether relation-based capture can occur outside of the attentional window, and thus cannot support the global selection of relation-based attention.…”
mentioning
confidence: 92%
“…A recent study (Goldstein & Beck, 2016) showed that a relation-matched distractor can capture attention even in inattention blindness. Researchers asked participants to count the number of times gray letters (T or L) bounced off the sides of a central box while ignoring either white or black letters.…”
mentioning
confidence: 99%